Study on Menstrual Hygiene Management among Urban and Rural Adolescent Girls in Marathwada region of Maharashtra, India - Fatima, Mahvish; Kausar, Heena; Giri, Purushottam; Ingale, Abhijeet (Indian Journal of Community Health, 2023)
Introduction: Adolescence is a significant period in the life of a woman. Menstruation is a naturally occurring physiological phenomenon in adolescent girls and premenopausal women. Menstrual hygiene and management is an insufficiently acknowledged issue and has not received adequate attention. The lack of menstrual hygiene among rural population is alarming, and there is a need for policy-making and awareness programs to be initiated. Aim: Hence the present study was aimed to compare the status of menstrual hygiene among rural and urban adolescent girls. Methods: A community-based cross-sectional study was carried out among 250 adolescent girls (rural & urban), aged between 13 to 19 years residing the in field practice area of IIMSR Medical College, Badnapur, Jalna. Data was analyzed by using MS Excel 2010. Results: Out of 250 participants, 48.8% girls from rural area and 51.2% from urban area. The mean age of the menarche was 12.3 ± 1.4 and 12.34 ± 1.43 in rural and urban girls, respectively. Knowledge of menstruation prior to menarche was found to be less in rural girls compared with urban girls. Regarding menstrual hygiene practices during menstruation, out of the total girls residing in rural area 49.18% girl and out of the total girls residing in urban area 62.5% girls were using sanitary pads. Restriction during menstruation was observed more in rural girls than in urban areas. Conclusion: More awareness regarding menarche and menstruation was among urban girls than. Hygienic practices observed by girls were also more satisfactory in the urban area as compared with rural ones.